2014
DOI: 10.1007/s13361-013-0776-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Documentation of Glycan Epitopes: Sequential Mass Spectrometry and Spectral Matching

Abstract: Documenting mass spectral data is a fundamental aspect of accepted protocols. In this report we contrast MSn sequential disassembly spectra obtained from natural and synthetic glycan epitopes. The epitopes considered are clusters found on conjugate termini of lipids and N-, and O-glycans of proteins. The latter are most frequently pendant through a CID-labile HexNAc glycosidic linkage. The synthetic samples were supplied by collaborating colleagues and commercial sources and usually possessed a readily release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 51 publications
(52 reference statements)
2
45
0
Order By: Relevance
“…For internal Fuc-LacNAc units, spectrum matching with standards has indicated that these structures match very well with the B/Y-type Fuc-LacNAc trisaccharide fragment isolated for sialylated Lewis X standards. This sim- ilarity essentially indicates that this unit is an internal Lewis X structure, and the m/z 646 fragmentation matches that standard trisaccharide spectrum (12). The isomeric mixture spectrum isolated from HMG-51 is shown in Fig.…”
Section: Ms N Analysis Of Human Milk Glycans Recognized By Rotavirusessupporting
confidence: 61%
See 4 more Smart Citations
“…For internal Fuc-LacNAc units, spectrum matching with standards has indicated that these structures match very well with the B/Y-type Fuc-LacNAc trisaccharide fragment isolated for sialylated Lewis X standards. This sim- ilarity essentially indicates that this unit is an internal Lewis X structure, and the m/z 646 fragmentation matches that standard trisaccharide spectrum (12). The isomeric mixture spectrum isolated from HMG-51 is shown in Fig.…”
Section: Ms N Analysis Of Human Milk Glycans Recognized By Rotavirusessupporting
confidence: 61%
“…Fucose localization, branching/ topology, linkages, and other epitope structure assignments are similar for all (23).…”
Section: Ms N Analysis Of Human Milk Glycans Recognized By Rotavirusesmentioning
confidence: 78%
See 3 more Smart Citations